OSGOOD SCHLATTER'S DISEASE IN YOUNG BASKETBALL PLAYERS - Snežana Bijelić; Milorad Maran; Slobodan Simović; Predrag Grubor; Jakovljević Aleksandar; Dario Kalacun (University of Banja Luka, Faculty of physical education and sport, 2010)
In this work is presented the experience with Osgood Schlatters disease in young male basket-ball players. From one overall number of 257 young male basketball players with ages between 10and 16 years is found that 23 or 8.9% had Osgood Schlatters disease. In control group of 250young males (10-16 years) without sport activities is found 4 % of Osgood Schlatters disease.All patients were treated with rest of training and sports activities and after that with phys-ioterapy. After 6 months everybody were allowed to have a full practice without clinical and radi-ological signs of disease.Stronger physical activities in an early adolescent's period are one of main factors of appearingof Osgood Schlatters disease.